ANALISIS BIAYA PERSEMAIAN PERMANEN BPTH DINAS KEHUTANAN PROVINSI KALIMANTAN SELATAN - Eka Aprilia Rahma Purbasiwi; Daniel Itta; Muhammad Helmi (Jurnal Sylva Scienteae, 2022)
This study aims to analyze the costs incurred in operating the nursery and to analyze the level of achievement of Break Even Point and Return of Investment, so that it is known whether the construction of a permanent nursery by BPTH Forestry Service of South Kalimantan Province is profitable. The data used in this study are primary data obtained through interviews and also secondary data that obtained from agencies, also journals and related research as support. The data analysis that used in this research is BEP analysis and ROI analysis. The results showed that the level of seedling production in 2020 was 2,155,973 with a total cost of Rp.2,315,742,703. Of the total seed production, the assumption of revenue in 2020 is IDR 4,546,102,200 with a BEP of Rp. 1,485,037,631. The BEP of seed production units in 2020 is at 813,554, with a total production of 2,155,973 seeds, so production exceeds the BEP. The result of the estimated revenue that exceeds the total cost, shows that the Return Of Investment in 2020 can be achieved with a figure of 88.8%.  These results indicate that this permanent nursery is considered feasible and also profitable